Mystical Kejawen in Satu Suro Film - Dewi Agustina Pratiwi; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2021)
Film is one of the electronic mass communication media in the form of audio-visual and mass in nature. Films are able to have a significant effect in conveying messages so that they affect people's mindsets. Film as a form of representation of social reality is packaged with various kinds of symbols and signs through each scene that can indirectly manipulate reality or commonly known as hyperreality. This study uses the film Satu Suro as the object of research. The purpose of this research is to describe and explain the mystical form of kejawen in Satu Suro film. Satu Suro film was chosen because it has a horror genre that carries the form of Javanese mysticism and is presented with a picture that exceeds the actual reality. This study uses a qualitative-descriptive approach. The method of data analysis in this study uses the mystical theory of kejawen which is associated with the semiotic theory of Charles Sanders Peirce. The results of this study indicate that the Satu Suro film contains elements of Javanese mysticism which are presented through six scenes. In this study, it is also concluded that the results of the analysis of the forms of Sign, Object, and Interpretant from Charles Sanders Peirce's semiotic model give rise to a form of kejawen mystical hyperreality which is very clearly depicted, how the reality of kejawen mysticism in real life is manipulated and constructed through signs and symbols that go beyond the real reality shown in this film.